Artificial Intelligence and Health-Seeking Behaviors of Educated Youth: A Critical Appraisal - Qamar, Saadia; Muslim, Imran (sourcecoder, 2025)
Artificial intelligence (AI) is advancing at an extraordinary pace to transform various modern fields of life including healthcare decision-making processes as well. Main Objective of the study was to unfold the unsighted use of AI in the critical field of health-care. It is a quantitative study, exploratory in nature, in the field of healthcare technology adoption. This study explored the habits of educated young ones for using techniques and having effects of AI for health-care. A survey of 200 participants disclosed that majority of the respondents found AI-based health tools valuable for quick advice and only 29% of them verified the information with a healthcare provider. Study showed that artificial intelligence works as a tool to assist healthcare delivery but it is not a substitute of doctor. It is recommended that some parameters must be laid out to limit the unguided use of AI in this perilous field.